JASPAR 2020: update of the open-access database of transcription factor binding profiles. Issue Volume 48:Issue D1(2020) (8th November 2019) - Fornes, Oriol; Castro-Mondragon, Jaime A; Khan, Aziz; van der Lee, Robin; Zhang, Xi; Richmond, Phillip A; Modi, Bhavi P; Correard, Solenne; Gheorghe, Marius; Baranašić, Damir; Santana-Garcia, Walter; Tan, Ge; et al.
Abstract: JASPAR (http://jaspar.genereg.net ) is an open-access database of curated, non-redundant transcription factor (TF)-binding profiles stored as position frequency matrices (PFMs) for TFs across multiple species in six taxonomic groups. In this 8th release of JASPAR, the CORE collection has been expanded with 245 new PFMs (169 for vertebrates, 42 for plants, 17 for nematodes, 10 for insects, and 7 for fungi), and 156 PFMs were updated (125 for vertebrates, 28 for plants and 3 for insects). These new profiles represent an 18% expansion compared to the previous release. JASPAR 2020 comes with a novel collection of unvalidated TF-binding profiles for which our curators did not find orthogonal supporting evidence in the literature. This collection has a dedicated web form to engage the community in the curation of unvalidated TF-binding profiles. Moreover, we created a Q&A forum to ease the communication between the user community and JASPAR curators. Finally, we updated the genomic tracks, inference tool, and TF-binding profile similarity clusters. All the data is available through the JASPAR website, its associated RESTful API, and through the JASPAR2020 R/Bioconductor package.